The mediating role of caffeine and biological age in the association between dietary index for gut microbiota and osteoporosis - Li, Yaxiong; Cao, Hong; Zhang, Jingyuan (Frontiers in Nutrition, 2025)
BackgroundThe Dietary Index for Gut Microbiota (DI-GM) is a novel metric developed to evaluate the diversity of intestinal microbiota. However, its relationship with osteoporosis remains uncertain.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2018. The DI-GM score was derived from two 24-h dietary recall interviews, while bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (QDR 4500A). Osteopenia and osteoporosis were diagnosed according to the World Health Organization (WHO) criteria. Age-standardized incidence rates (ASIRs) were calculated through direct standardization to the 2,000 U. S. standard population. Additionally, the study employed multivariate logistic regression, restricted cubic spline (RCS) analysis, mediation analysis, and subgroup analysis to explore the data comprehensively.ResultsWeighted logistic regression analysis revealed that higher DI-GM scores were significantly negatively associated with the risk of osteoporosis. Compared to the Q1 group, the Q4 group exhibited a significantly reduced risk of osteoporosis (OR = 0.781, 95% CI: 0.693–0.869). RCS curve analysis identified a nonlinear relationship between DI-GM and osteoporosis, with a critical inflection point at 3.9. Mediation analysis demonstrated that Phenotypic Age (PA), Klemera-Doubal Method (KDM) and caffeine mediated 4.73, 4.55, and 20.33% of the association between DI-GM and osteoporosis, respectively. Furthermore, age-standardized incidence rate analysis showed that the ASIR of osteoporosis was highest among women aged 60–79 years (65.09%). The ASIR for Non-Hispanic Black individuals was significantly lower compared to other racial groups.ConclusionHigher DI-GM scores were associated with a reduced risk of developing osteoporosis, with biological age and caffeine serving as mediators in this relationship.